Gut microbiome features in pediatric food allergy: a scoping review - Farnetano, Margherita; Carucci, Laura; Coppola, Serena; Oglio, Franca; Masino, Antonio; Cozzolino, Marica; Nocerino, Rita; Berni Canani, Roberto (Frontiers in Allergy, 2024)
Increasing evidence suggests that alterations in the gut microbiome (GM) play a pivotal role in the pathogenesis of pediatric food allergy (FA). This scoping review analyzes the current evidence on GM features associated with pediatric FAs and highlights the importance of the GM as a potential target of intervention for preventing and treating this common condition in the pediatric age. Following the Preferred Reporting Items for Systematic Reviews and Meta-Analysis guidelines, we searched PubMed and Embase using the keywords (gut microbiome OR dysbiosis OR gut microbiota OR microbiome signatures) AND (food allergy OR IgE-mediated food allergy OR food protein-induced allergic proctocolitis OR food protein-induced enterocolitis OR non-IgE food allergy OR cow milk allergy OR hen egg allergy OR peanut allergy OR fish allergy OR shellfish allergy OR tree nut allergy OR soy allergy OR wheat allergy OR rice allergy OR food sensitization). We included 34 studies reporting alterations in the GM in children affected by FA compared with healthy controls. The GM in pediatric FAs is characterized by a higher abundance of harmful microorganisms (e.g., Enterobacteriaceae, Clostridium sensu stricto, Ruminococcus gnavus, and Blautia spp.) and lower abundance of beneficial bacteria (e.g., Bifidobacteriaceae, Lactobacillaceae, some Bacteroides species). Moreover, we provide an overview of the mechanisms of action elicited by these bacterial species in regulating immune tolerance and of the main environmental factors that can modulate the composition and function of the GM in early life. Altogether, these data improve our knowledge of the pathogenesis of FA and can open the way to innovative diagnostic, preventive, and therapeutic strategies for managing these conditions.